Village Content Creator Training for Santong Village Youth - Muhammad Mahfuz; Noni Antika Khairunnisah; Ahmad Ahmad; Irma Aliana Putri (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2024)
Village Content Creator Training for Santong Village Youth aims to empower the younger generation through mastering digital skills in creating creative content. In the increasingly developing digital era, the ability to produce interesting and quality content has become an important skill for promoting local potential. This training covers fundamental aspects such as photography techniques, videography, content editing, and marketing strategies via social media. The implementation methods used consist of counseling, practical workshops, field simulations, and evaluation of feedback from participants. Training results showed significant improvements in participants' digital skills, with 80% of participants feeling more confident in creating content. Apart from that, participants succeeded in producing various types of content that reflected the unique culture and tourism potential of Santong Village. The formation of a local content creator community is also an important outcome of this training, which is expected to support collaboration and innovation in the future. Overall, this training makes a positive contribution to youth empowerment and local economic development through the use of digital technology.